Maternal varicella antibodies in children aged less than one year: Assessment of antibody decay - Bolotin, Shelly; Hughes, Stephanie L.; Savage, Rachel D.; McLachlan, Elizabeth; Severini, Alberto; Arnold, Callum; Richardson, Susan; Crowcroft, Natasha S.; Deek, Shelley; Halperin, Scott A.; Brown, Kevin A.; Hatchette, Todd; et al. (PloS one, 2023)
To investigate maternal antibody levels to varicella in infants <12 months of age in Ontario, Canada. In this study, we included specimens from infants <12 months of age, born at [greater than or equal to]37 weeks gestational age, who had sera collected at The Hospital for Sick Children (Toronto, Canada) between 2014-2016. We tested sera using a glycoprotein-based enzyme-linked immunosorbent assay (gpELISA). We measured varicella susceptibility (antibody concentration <150mIU/mL) and mean varicella antibody concentration, and assessed the probability of susceptibility and concentration between one and 11 months of age using multivariable logistic regression and Poisson regression. We found that 32% of 196 included specimens represented infants susceptible to varicella at one month of age, increasing to nearly 80% at three months of age. At six months of age, all infants were susceptible to varicella and the predicted mean varicella antibody concentration declined to 62 mIU/mL (95% confidence interval 40, 84), well below the threshold of protection. We found that varicella maternal antibody levels wane rapidly in infants, leaving most infants susceptible by four months of age. Our findings have implications for the timing of first dose of varicella-containing vaccine, infection control measures, and infant post-exposure prophylaxis recommendations.